2017
DOI: 10.1177/1075547017696165
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science as a Means for Increasing Public Engagement in Science

Abstract: Citizen science is often assumed to increase public science engagement; however, little is known about who is likely to volunteer and the implications for greater societal impact. This study segments 1,145 potential volunteers into six groups according to their current engagement in science (EiS). Results show groups with high levels of EiS are significantly more interested in volunteering and more likely to participate in various research roles than those with lower EiS scores. While citizen science benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 64 publications
1
48
0
1
Order By: Relevance
“…The hypothesis of this research supports those of some of the previous studies which found a positive association between volunteers' Science Trust and their intention to volunteer (Martin, 2017). The findings of this research indicate that the science volunteers were positively motivated across cases, either intrinsically or due to their personal trust, meaning that if they think all scientific data are objective and reliable, they will have greater willingness to attend Science Volunteer activities rather than other activities in the future.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The hypothesis of this research supports those of some of the previous studies which found a positive association between volunteers' Science Trust and their intention to volunteer (Martin, 2017). The findings of this research indicate that the science volunteers were positively motivated across cases, either intrinsically or due to their personal trust, meaning that if they think all scientific data are objective and reliable, they will have greater willingness to attend Science Volunteer activities rather than other activities in the future.…”
Section: Discussionsupporting
confidence: 86%
“…In this research, it is considered that, if volunteers have more trust in science, they will usually be involved in citizen science. Unfortunately, the literature on the effects between trust in science and involvement in citizen science is limited (Martin, 2017). Thus, in this research, this effect was tested by examining the factors that influence volunteers' trust in science and what impacts their trust has on their intentions to continue their involvement in volunteer work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It may help to articulate the values of the most affected communities and align policy recommendations with their expectations (Lemke and Harris-Way, 2015). Further, citizens have recently become more involved in the research effort itself through do-it-yourself science and other bottom-up approaches (Nascimento et al 2014;Martin 2017).…”
mentioning
confidence: 99%
“…Contributing to CS efforts presents one type of action people can take. However, evidence suggests the people most interested in CS programs are those already concerned about science and the environment (Martin, 2017), meaning that CS will naturally attract a particular type of participant (pro-science or pro-environmental) rather than a broad reach across audiences with many different science/environmental attitudes. Furthermore, one of the challenges in CS projects is to recruit and retain participants.…”
Section: Importance Of Public Preferences For Participation In Citizementioning
confidence: 99%